2016
DOI: 10.1017/jog.2016.54
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying volume loss from ice cliffs on debris-covered glaciers using high-resolution terrestrial and aerial photogrammetry

Abstract: Mass losses originating from supraglacial ice cliffs at the lower tongues of debris-covered glaciers are a potentially large component of the mass balance, but have rarely been quantified. In this study, we develop a method to estimate ice cliff volume losses based on high-resolution topographic data derived from terrestrial and aerial photogrammetry. We apply our method to six cliffs monitored in May and October 2013 and 2014 using four different topographic datasets collected over the debris-covered Lirung G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
109
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 84 publications
(122 citation statements)
references
References 26 publications
10
109
1
Order By: Relevance
“…These images were analysed with an SfM procedure similar to that of the UAV data, and processed with 21 on-glacier GCPs to derive an orthomosaic and DEM ( Table 2; Brun, 2015;Brun et al, 2016). The resulting DEM was evaluated with 682 differential global positioning system (dGPS) points taken on prominent sections of the glacier; the mean absolute vertical error at these points was 0.5 m. However, the source photos and GCPs are not uniformly distributed, with the highest density near the study ponds, so we assume an uncertainty of 1 m for the whole dataset (Brun et al, 2016). The terrestrial survey area was slightly larger than for the UAV surveys, but did not include the uppermost portion of the tongue for safety considerations.…”
Section: Orthoimages and Demsmentioning
confidence: 99%
“…These images were analysed with an SfM procedure similar to that of the UAV data, and processed with 21 on-glacier GCPs to derive an orthomosaic and DEM ( Table 2; Brun, 2015;Brun et al, 2016). The resulting DEM was evaluated with 682 differential global positioning system (dGPS) points taken on prominent sections of the glacier; the mean absolute vertical error at these points was 0.5 m. However, the source photos and GCPs are not uniformly distributed, with the highest density near the study ponds, so we assume an uncertainty of 1 m for the whole dataset (Brun et al, 2016). The terrestrial survey area was slightly larger than for the UAV surveys, but did not include the uppermost portion of the tongue for safety considerations.…”
Section: Orthoimages and Demsmentioning
confidence: 99%
“…The direct atmosphere-ice interface can result in significantly higher ablation rates relative to the surrounding debris-covered area and are therefore areas of interest when solving for glacier melt in heavily debris-covered regions (Buri et al, 2016b;Thompson et al, 2016;Brun et al, 2016). The mechanism(s) of ice cliff formation, the controls of ice cliff migration patterns and ice cliff residence time on a glacier are gaining research attention but are still poorly understood processes, in part, due to a lack of base data (Reid and Brock, 2014;Watson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism(s) of ice cliff formation, the controls of ice cliff migration patterns and ice cliff residence time on a glacier are gaining research attention but are still poorly understood processes, in part, due to a lack of base data (Reid and Brock, 2014;Watson et al, 2017). Melt and surface energy fluxes at specific ice cliffs have been studied in detail (Sakai et al, 1998;Han et al, 2010;Sakai et al, 2002;Reid and Brock, 2014;Buri et al, 2016a) and digital elevation model (DEM) differencing has shown the spatial trends of enhanced glacier melt relative to surrounding debris cover and ice cliff evolution at the scale of several cliffs or a single glacier tongue (Thompson et al, 2016;Brun et al, 2016). All of the studies mentioned suggest that ice cliffs, if present on a debris-covered glacier, need to be accounted for in order to adequately model glacier mass loss and response to climate.…”
Section: Introductionmentioning
confidence: 99%
“…The direct atmosphereice interface can result in significantly higher ablation rates relative to the surrounding debris-covered area (Buri et al, 2016b;Thompson et al, 2016;Brun et al, 2016). The mechanism(s) of ice cliff formation, the controls of ice cliff migration patterns and ice cliff residence time on a glacier are gaining research attention but are still poorly understood processes and a present 15 lack of base data is an obstacle to establishing a robust understanding (Reid and Brock, 2014;Watson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism(s) of ice cliff formation, the controls of ice cliff migration patterns and ice cliff residence time on a glacier are gaining research attention but are still poorly understood processes and a present 15 lack of base data is an obstacle to establishing a robust understanding (Reid and Brock, 2014;Watson et al, 2017). Melt and surface energy fluxes at specific ice cliffs have been studied in detail (Sakai et al, 1998;Han et al, 2010;Sakai et al, 2002;Reid and Brock, 2014;Buri et al, 2016a) and digital elevation model (DEM) differencing has shown the spatial trends of enhanced glacier melt relative to surrounding debris cover and ice cliff evolution at the scale of several cliffs or a single glacier tongue (Thompson et al, 2016;Brun et al, 2016). All of the studies mentioned suggest that ice cliffs, if present within a debris 20 cover, need to be accounted for in order to adequately model glacier mass change and response to climate.…”
Section: Introductionmentioning
confidence: 99%